HUBUNGAN STATUS GIZI TERHADAP KEMAMPUAN MOTORIK DI SD NEGERI 17 KOTO IV AUR MALINTANG KABUPATEN PADANG PARIAMAN - Hilda Oktri Yeni; Fadli Surahman (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
This research aims to find out how big the relationship of nutritional status against motor ability of elementary school students 17 IV Koto Aur Malintang Padang Pariaman Regency.This type of research is co relational. The populations in this research are students of elementary school 17 IV Koto Aur Malintang Padang Pariaman Regency. There are 115 students and a sample is taken only son and 22 students by using purposive sampling technique. Technique Data analysis is using product moment correlation analysis.The result obtained from this research is the correlation significant between the nutritional status and motor skills. And this is evidenced from rcount = 0.748 rtable at α = 0.05 = 0.423. The conclusion of the research if there is a significant relationship between the nutritional status and motor skills in elementary school 17 IV Koto Aur Malintang Padang Pariaman Regency.